The Effects of Overvoltage Aging on 20 kV XLPE Power Cable - Uydur, Cihat Cagdas; Arikan, Oktay; Kucukaydin, Baris; Dursun, Bekir; Kumru, Celal Fadil (IEEE, 2019)
XLPE power cables have been widely used with the development of city power grid because of their obvious advantages. To improve the reliability of power supplies and meet the requirements of urban landscaping, however, faults in the electricity distribution grid and load/demand imbalance cause degradation in underground cables. This degradation leads the cable to be aged and reduce its lifetime. Therefore, it is important to examine the behavior of the XLPE insulated cable dielectric parameters. In this study, a 12/20 kV XLPE cable was aged using 60 kV overvoltage and this voltage was applied to the test samples for 15 minutes intervals. 80 cycles of aging were carried out and dissipation factor (tan delta), dielectric losses (P-k) and partial discharge (PD) measurements were performed after each aging cycle. OMICRON CPC100/CPTD1 was used to measure dissipation factor (tans), dielectric losses (Pk) and OMICRON MPD600 was used to measure partial discharge.
Keywords: Engineering